Our patients, our ’cases’ - Shankar, P Ravi (Research and Humanities in Medical Education, 2021)
In busy teaching hospitals, patients are often regarded as ‘cases’ and the human dimensions are sometimes neglected. In this article, I describe a few of my experiences at the Government Medical College, Thrissur, during my undergraduate medical education days. Patients were examined repeatedly, and many were very uncomfortable with this. During those days there were no facilities for simulation and even procedures were ‘learnt’ on patients. The hospital environment did not provide enough space and privacy to patients and was confusing and bureaucratic. We were not explicitly taught communication skills and how to understand the patient perspective. This paper suggests that the health humanities can play an important role in understanding the patient perspective.